Chemistry of free radicals produced by oxidation of endogenous α-aminoketones: a study of 5-aminolevulinic acid and α-aminoacetone by fast kinetics spectroscopy - Morlière, P. (2022)
© 2014 Elsevier B.V. All rights reserved.